Configuración multicriterio de células de fabricación considerando efecto sobre planes de producción - Orejuela Cabrera, Juan Pablo; Castillo Zapata, Adriana María; Gill Gonzáles, Cristiam Andres (Scientia et Technica, 2019)
In competitive markets, flexibility is a key requirement to compete, group technology allows you to obtain this flexibility at a low cost, because it combines the advantages of mass production with the advantages of production by workshops Objective. Create a methodology that integrates the plans of: plant configuration, capacity and production, evaluating multiple criteria to select the grouping alternatives with better results. Materials and methods, five stages are articulated to achieve the objective: a. Creation of product families, b. Configuration of plant, capacity and production, c. Estimation of performance measures and d. Process of hierarchical analysis. Results: A consistent methodology is achieved regarding the sensitivity of the AHP evaluation of the performance measures, the individual variations in the criteria of the candidate configurations do not modify the decision found (configuration to be selected). Conclusion. It is possible to address the problem of cell formation considering an approach in which the problem is broken down into less complex sub-problems and thus include multiple grouping criteria at the time oriented to the environment where the methodology is applied.